PENGARUH BIAYA BAHAN BAKU, BIAYA TENAGA KERJA LANGSUNG DAN FACTORY OVERHEAD COST TERHADAP PENINGKATAN HASIL PRODUKSI PADA PERUSAHAAN KECIL INDUSTRI TAHU TEMPE DI KOTA BATAM - Baru Harahap; Argo Putra Prima (LPPM Universitas Putera Batam, 2019)
The purpose of this research is to determine the effect To determine the effect of the cost of raw materials, direct labor costs and factory overhead costs on the increase in production results in small companies in the tempeh tofu industry in Batam City. The sampling method is carried out based on several reasons with the technique used namely porposive sampling to determine the sample with certain considerations. As for the research criteria as follows: (1). Small tofu industry companies registered before 2013-2017; (2). Companies listed during the period 2013 - 2017; (3). Complete financial statements as of December 31 2013-2017. The results of this study have a significant effect on raw materials, direct labor costs and factory overhead costs on production results in small companies in the tempeh tofu industry in Batam City with significant values of 0,000, 0,003 and 0,038 <0,05, respectively. While simultaneous raw materials, direct labor costs and factory overhead costs have a significant effect on production results in small companies in the tempeh tofu industry in Batam City with a significant value of 0,000 <0,05.